ANALISIS PRAGMATIK TARI DRIASMARA - Maryono Maryono (Gelar : Jurnal Seni Budaya, 2013)
This paper aims to reveal the meaning of Driasmara dance presented in Javanese cultural weddingrituals ceremonies from a pragmatics perspective. The methodology used was qualitative research.Theoretical base utilized is pragmatic theory for analyzing its linguistic component and supportedwith performing arts theory to examine the non–linguistic components. Pragmatics is a subdisciplineof linguistics that linking language with the symbol system, linking with the languageusers. Pragmatics deals with the use of language, that is how the language is used by speakers ofthe language in the actual interaction situation, not in the abstracted situation, that were set up bylinguists (Asim Gunarwan, 2005: 1). In communication the language used can be both formal andpragmatic. Pragmatic language form is also used in daily communication along with the usageinthe arts environment such as wayangs, kethoprak, Langendriyan, dances, and others. The rationaleis that this form of dance consists of linguistic verbal and nonverbal components, both are symbolsystems . Based on a pragmatic analysis of the Driasmara Dance there is a finding that DriasmaraDance is a form of couples romance dance refers to the Panji Saga that are expected to befollowed by a bride and groom and the community as the large audiences. Romance that waspictured in the Driasmara Dance is directed to be more representing the life directed to therepresentative of the life of people in love. Hopefully the language will be easily captured andmodeled by the bride and the groom.